Characterization of plasma and emergent ion beam in a compact helicon source with permanent magnets - Virko, Yu.V.; Virko, V.F.; Shamrai, K.P.; Yakimenko, A.I. (Вопросы атомной науки и техники, 2007)
A compact helicon source with multi-component changeable magnetic system was studied to gain enhanced parameters of plasma and emergent ion beam. Alteration of the magnetic field configuration was found to be the main instrument for increasing the plasma density and ion beam current. The source efficiency was also critically dependent on the rf antenna position and Ar gas pressure. By optimizing these parameters, plasma outflow was greatly increased and the emergent ion beam of energy above 100 eV was produced. Досліджено компактне геліконне джерело з багатокомпонентною змінюваною магнітною системою з метою одержання поліпшених параметрів плазми та вихідного іонного пучка. Зміна магнітної конфігурації виявилась основним засобом для підвищення густини плазми та струму іонного пучка. Ефективність джерела також критично залежала від розташування ВЧ- антени та тиску аргона. Шляхом оптимізації цих параметрів був істотно підвищено вихід плазми та одержано вихідний пучок іонів з енергіями понад 100 еВ. Исследован компактный геликонный источник с многокомпонентной изменяемой магнитной ситемой с целью получения улучшенных параметров плазмы и выходящего ионного пучка. Изменение магнитной конфигурации оказалось основным средством для повышения плотности плазмы и тока ионного пучка. Эффективность источника также критически зависела от положения ВЧ- антенны и давления аргона. Путем оптимизации этих параметров был существенно повышен выход плазмы и получен выходящий пучок ионов с энергиями свыше 100 эВ.